Pengembangan Instrumen Skala Perkembangan Komunikasi Nonverbal pada Anak Usia 0-18 Bulan - Ginantaka, Hendra; Sudarman, Sudarman (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Most children miss the opportunity to receive developmental assessments due to a lack of screening tools. Assessment instruments are a problem that must be resolved immediately and early detection efforts are key in preventive and habilitative programs. Currently there is no valid and reliable instrument to measure the development of nonverbal communication in children. Objective: This research aims to develop an assessment instrument for the Nonverbal Communication Development Scale (SPK-Nv) and test whether the instrument is valid and reliable in measuring nonverbal abilities in children aged 0-18 months in Sananwetan District, Blitar City. Method: The type of research used is quantitative descriptive research. Test logical validity through Expert Judgment using Itemrated Content Validity Index (I-CVI) analysis and logical reliability using Inter-Rater Reliability (IRR). Then it was tested on a sample of typical children aged 0-18 months using Simple Random Sampling with a total of 161 children as respondents. Validity test uses Pearson product moment correlations and Reliability Test uses Cronbach's Alpha. Thesis Results: The Development Stage SPK-Nv instrument consists of 40 question items. Testing content validity through Expert Judgment with I-CVI analysis obtained a relevance value of 1.00 and Inter-Rater Reliability (IRR) Kappa Fleiss with a value of 0.298, so it means that the items in the SPK-Nv Instrument are relevant and reliable with a Fair level of agreement. The next stage, SPK-Nv was tested on 161 samples. As a result, the SPK-Nv instrument has 35 valid and reliable question items to measure nonverbal communication skills in children aged 0-18 months in Sananwetan Blitar sub-district. Conclusion: The SPK-Nv instrument that has been developed and prepared has 35 valid and relevant question items for measuring nonverbal communication skills in children aged 0-18 months in Sananwetan District, Blitar City. Keywords: Development of Nonverbal Communication, in children, Early Childhood Language Development, Preverbal, Prelinguistic skills